Dietary Salvia officinalis leaves enhances antioxidant-immune-capacity, resistance to Aeromonas sobria challenge, and growth of Cyprinus carpio. Issue 127 (August 2022) - Abdel Rahman, Afaf N.; Van Doan, Hien; Elsheshtawy, Hassnaa Mahmoud; Dawood, Ali; Salem, Shimaa M.R.; Sheraiba, Nagwa I.; Masoud, Shimaa R.; Abdelnaeim, Noha S.; Khamis, Tarek; Alkafafy, Mohamed; Mahboub, Heba H.
Abstract: The current perspective is a pioneer to assess the efficacy of Salvia officinalis leave powder (SOLP) on growth, intestinal enzymes, physiological and antioxidant status, immunological response, and gene expression of Common carp ( Cyprinus carpio ). We also looked into fish resistance after being challenged with Aeromonas sobria, a pathogenic zoonotic bacteria. Fish (N = 120) were fed four different experimental diets in triplicate for 8 weeks. The control diet (SOLP0 - without SOLP); meanwhile, the other three diets included SOLP of 2, 4, and 8 g kg −1 concentrations (SOLP2, SOLP4, and SOLP8), respectively. Findings demonstrated that fish fed SOLP4 and SOLP8 diets had better growth performance and improved digestion by noticeable enhancing lipase and amylase enzymes activity than other groups. Additionally, the antioxidant (superoxide dismutase and glutathione peroxidase) and immune activities (immunoglobulin M, nitric oxide, and antiprotease) clarified a significant increase (p < 0.05) in SOLP4 and SOLP8 groups. Enriched diets with SOLP4 and SOLP8 exhibited better expression of splenic genes ( IL-1β, IL-6, IL-10, TLR-2, and SOD ), intestinal genes ( Slc26a6 ) and ( PepT1 or Slc15a1 ), and muscular genes ( IGF-1 and SOD ), while MSTN was down-regulated. After 8 weeks of the experimental trial, C. carpio challenged by A. sobria exhibited the highest cumulative mortality (66.67%), while SOLP8-dietary intervention showed the best results in enhancing the fish resistance against A. sobria by lessening mortalities to 13.33% followed by SOLP4 diet (20%). The outcomes indicate that the expression of splenic, muscular, and intestinal genes confirm the efficacy of SOLP on enhancing growth, digestion, and immune-antioxidant status, and recommend the potential use of SOLP especially at 4 g kg −1 level as a valuable natural economic diet additive in C. carpio culture for sustaining aquaculture. Highlights: Dietary Salvia officinalis leaves powder (SOLP) enhances growth and digestion in Cyprinus carpio. Diet supplement with SOLP modulates antioxidant-immune-capacity. Dietary intervention of SOLP enhances resistance against Aeromonas sobria infection. A supplemented diet with SOLP up-regulates the expression of different genes.